ENHANCING STUDENTS’ ACHIEVEMENT IN WRITING TEXT USING GROUP INVESTIGATION METHOD - Jenny Ika Misela; Mahendra Puji Permana Aji (Suluh Adiluhung Publisher (SAPub), 2025)
Writing is considered by students as a difficult skill to study. They do not realize that communication can be transferred through writing. Consequently, they write without purpose and in disorder way. They only write what is inside their head down in the paper and ignore what their purpose is, its grammatical and vocabulary use. Group Investigation (GI) is an organizational approach that allows a class to work actively and collaboratively in small groups and enables students to take an active role in determining their own learning goals and processes. GI is interesting so that the students will feel the new atmosphere in classroom and they are interested in learning writing. This study aims to investigate the implementation of GI to enhance the students’ writing ability. This study was conducted by using classroom action research that has two cycles within. The subject of the research was the students of eleventh year SMKN 2 Kediri which consisted of 35 students. The instruments of collecting data were quantitative (writing test) and qualitative data (observation sheet, and field notes). Questionnaire and interview being used by the researcher to know deeply the problem faced by the students then she analyzed them to find the appropriate method. They could follow the writing process from (1) topic selection, (2) cooperative planning, (3) implementation, (4) analysis and synthesis, (5) presentation of final project, and (6) evaluation. Based on the writing test scores, the students’ score kept improving in every test. In the pre-liminary study, there were only 43% of the students who passed the minimum standard score. After giving treatment to the students using GI, there was an enhancement towards the students writing. 91% of the students passed the test in cycle 1 and 100% of the students passed the test in cycle 2. Based on the observation sheet and field notes, it was found that the learning process of writing ran well. The students can be more active in group work, and they can follow the process of writing well-ordered by implementing the steps of GI. The result of the research showed that GI method could enhance students’ achievement in writing instruction text. It was suggested to modify and make the GI method to be more interesting and suitable towards the skill and topic of the study.